Komposisi Komunitas Bakteri yang Berasosiasi dengan Karang Acropora hyacinthus - Anggraeni, Trisilia Mulyawati; Dirgayusa, I Gusti Ngurah Putra; Widiastuti, Widiastuti (Journal of Marine and Aquatic Sciences; Vol 8 No 1 (2022)DO - 10.24843/jmas.2022.v08.i01.p17, 2022)
Hard coral is the main constituent of the coral reef ecosystem and functions as shelter, nursery, and feeding ground for various marine macro- and microbiotas, such as bacteria in its mucus. Coral as the host may benefit from this partnership or receives detrimental effects since bacteria may turn into parasitic or pathogenic. Coral  A. hyacinthus  can be transplanted for ornamental coral. However, it is vulnerable to be infected by coral disease due to pathogenic bacteria if the water quality is poor. Therefore, this study was aimed to determined the community composition of bacteria associated with coral  A. hyacinthus  mucus. Corals  A. hyacinthus  were collected from the traditional coral transplantation in Patas village, Gerogak District, Buleleng Regency. Mucus were sampled from ± 5 cm fragment from 3 different coral colonies. Isolates were cultured in the Nutrient Agar medium. The identification of bacteria isolates was according to Biochemical Tests for Identification of Medical Bacteria 2nd edition. The identification of the isolates consisted of morphological and biochemical tests. The identification results found 10 isolates that consisted of  Micrococcus sp . Pseudomonas sp.,  Flavobacterium sp . and  Vibrio sp . However, the composition varied among the coral colonies.